SENTRA UMKM MODE - Agatha Lavinia; Martin Halim (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
Dwelling is a human respond for tha changes, but not all humans are ready for it. Humans who are not compatible enough will unable to compete with who are ready to take advantages for the changes especialy techologhy related. Likewise with the problem that accured in Tanah Sereal, Tambora, West Jakarta. Tanah Sereal has has many problem, one of wich isdie to the scattered location of the production house conduce limited opportunity for the buyers to determine existing production house. Apart from that, the pandemic effect the sales rate to decrease in Tanah Sereal. This leads manya production houses to change to online trading. Online Trading creates new problem for buyers because of the items are personalized they need to be tried on. To respond of these problem, it is necessary to agglomerate the production houses to make it easier for the prospective buyer to choose existing sellers. It also provide opportunities for buyers to try the purchased item so that fashion MSME center are creates. The choses theory is in the form of study of dwelling according to Christian Norbrg-Schulz, job training, MSMEs, and MSME centers. Desain method that is used is analysis-synthesis method based on region data and community activity patterns in Tanah Sereal. With fashion MSME center, it is hoped to solve the distribution location of production houses, provide conectivitu between visitors and production hoises to improve the image of Tanah Sereal. Keywords: Convection; Dwelling; Fashion MSME Center; Tanah Sereal AbstrakBerhuni merupakan cara manusia untuk merespon perubahan yang ada, namun tidak semua manusia siap akan adanya perubahan tersebut. Manusia yang tidak siap beradaptasi dengan kecanggihan teknologi akan kalah bersaing dengan manusia yang siap memanfaatkan kemajuan teknologi yang ada. Demikian halnya dengan permasalahan yang terjadi di daerah Tanah Sereal, Tambora, Jakarta Barat. Tanah Sereal memiliki banyak permasalahan salah satunya adalah dikarenakan lokasi rumah produksi yang tersebar menyebabkan membatasi kesempatan pembeli menentukan rumah produksi yang ada. Selain dari itu, pandemi mempengaruhi tingkat penjualan konveksi di tanah sereal hingga menurun. Hal ini menyebabkan banyak pedagang beralih ke perdagangan online. Perdagangan online menimbulkan masalah baru bagi bara pembeli karena barang yang dibeli bersifat personal sehingga butuh dicoba. Dalam merespon kedua permasalahan tersebut dibutuhkan pengelompokan rumah produksi untuk memudahkan pembeli memilih penjual yang ada dan memberikan kesempatan bagi pembeli mencoba barang yang dibeli sehingga sentra UKM mode tercipta. Kajian teori yang dipilih berupa kajian mengenai terori dwelling menururt Chistian Norberg-Schulz, teori everydayness, pelatihan kerja, UMKM, dan sentra UMKM. Metode perancangan yang dilakukan menggunakan metode analisis-sintesis berdasarkan data kawasan dan pola kegiatan masyarakat di Tanah Sereal. Dengan adanya sentra UMKM mode diharapkan dapat menyelesaikan masalah tersebarnya rumah produksi, memberikan konektivitas antar pengunjung dengan rumah produksi sehingga dapat meningkatkan citra kawasan Tanah Sereal.